Dungeons and Diabetes: co-design of an educational game to promote diabetes awareness - Filho, Airton; Honda, Fabrizio; Macena, Jeniffer; Lima, Márcia; Pessoa, Marcela; Pires, Fernanda (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2025)
Given the challenges related to a lack of knowledge about diabetes and low adherence to self-care practices, this work presents the initial proposal for the educational game Dungeons and Diabetes. Its development followed an educational game design process involving reviewing existing research and identifying learning gaps. We created the game in co-design with a student in computer science who has diabetes, and it aims to raise awareness through playful challenges that encourage reflection on daily care routines. The proposal incorporates principles from Multimedia Learning and Narrative Learning theories, resulting in a 2D proof of concept with mechanics and elements aligned with educational goals in the health context.